2023
DOI: 10.3390/polym15051114
|View full text |Cite
|
Sign up to set email alerts
|

Poly(methyl methacrylate) as Healing Agent for Carbon Fibre Reinforced Epoxy Composites

Abstract: Self-healing materials offer a potential solution to the problem of damage to fibre-reinforced plastics (FRPs) by allowing for the in-service repair of composite materials at a lower cost, in less time, and with improved mechanical properties compared to traditional repair methods. This study investigates for the first time the use of poly(methyl methacrylate) (PMMA) as a self-healing agent in FRPs and evaluates its effectiveness both when blended with the matrix and when applied as a coating to carbon fibres.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Compared to other studies that investigated the use of SAP in coatings, the particle size of the SAP used for this study has a wide distribution and is on the larger end (Figure 1). 9,11,12 Figure 2 shows the FE-SEM images of the SAP and it can be observed that the particles have compact grains, irregular morphology, and observable cracks at 30,000Â magnification, which are characteristics of SAPs comminuted in a grinder. 15,16…”
Section: Optical Microscopy and Fieldemission Scanning Electron Micro...mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other studies that investigated the use of SAP in coatings, the particle size of the SAP used for this study has a wide distribution and is on the larger end (Figure 1). 9,11,12 Figure 2 shows the FE-SEM images of the SAP and it can be observed that the particles have compact grains, irregular morphology, and observable cracks at 30,000Â magnification, which are characteristics of SAPs comminuted in a grinder. 15,16…”
Section: Optical Microscopy and Fieldemission Scanning Electron Micro...mentioning
confidence: 99%
“…The most recent study regarding the use of SAP in self-healing coating is by Peñas-Caballero et al 12 where they investigated the application of superabsorbent polymers in epoxy coating and studied the performance at the macro, micro, and sub-microscales using localized electrochemical techniques in saline solution. SAP of 10 wt% is mixed with the epoxy and the location of SAP in the coating is then varied on the surface, middle, and bottom of the coating.…”
Section: Introductionmentioning
confidence: 99%
“…The results of interlaminar shear test showed that although the addition of EMAA reduced the interlaminar shear strength of the composite, a healing efficiency of 109% was achieved after heating. Interestingly, Peñas-Caballero et al 81 have recently innovatively sprayed carbon fiber surfaces with EMAA. The advantages of this treatment included a marginal impact on the mechanical properties of CFRP and a significant improvement in the interlaminar fracture toughness by 260%, alongside a high healing efficiency of over 40%.…”
Section: Thermoplastic Additionmentioning
confidence: 99%
“…Excessive cracking increases the possibility of structural damage, making innovative solutions for repair and reinforcement necessary [3][4][5][6][7][8]. Traditional repair methods are limited in their ability to meet the requirements of modern engineering practices, prompting the search for novel approaches to address the challenges posed by deteriorating concrete [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%